Do we still need to study palonosetron for chemotherapy-induced nausea and vomiting? A cumulative meta-analysis. (October 2019) - Chow, Ronald; Aapro, Matti; Navari, Rudolph M.; Gralla, Richard; Chiu, Nicholas; Chiu, Leonard; Chan, Stephanie; Popovic, Marko; Lam, Henry; Lock, Michael; DeAngelis, Carlo
Abstract: Introduction: The aim is to conduct an updated systematic review comparing palonosetron to other 5-HT3 RAs for the prophylaxis of CINV, assess for publication biases, and determine whether further RCTs are required, that could potentially lead to a different meta-conclusion. Methods: Random-effects analysis model was used to generate odds ratio (OR), risk differences (RD) and accompanying 95% confidence intervals (CI). Funnel plots to assess for biases and cumulative meta-analyses to assess effect size over time were generated. Results: 4145 patients were randomized to palonosetron and 4911 received other 5-HT3 RAs. In the majority of efficacy endpoints, the meta-conclusion has not changed over time - recent clinical trials simply narrow CIs the meta-conclusion. Safety profile boasts a stable conclusion over time. No publication biases exist. Conclusion: Considering the vast amount of resources needed to conduct RCTs, resources should be dedicated to other prophylactic treatments/settings which have not been as well explored.